2021
DOI: 10.1093/rheumatology/keab128
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of E148Q heterozygous variant in paediatric familial Mediterranean fever

Abstract: Objectives Familial Mediterranean Fever (FMF) results from mutations in the Mediterranean fever (MEFV) gene. The p.E148Q is one of the most frequent protein alternations in the MEFV gene, yet the exact E148Q genotype–phenotype correlation remains unclear. The aim of this study was to examine clinical significance of heterozygous E148Q variant in a paediatric FMF cohort. Methods We compared the clinical manifestations and dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…E148Q was found to be the fourth most common mutation in our cohort. In a recent study by Tirosh et al ( 29 ), it was reported that the presence of the E148Q variant with the M694V variant was not worsening the clinical phenotype. However, M694V/E148Q mutation was found in three of the patients who did not respond to colchicine in our study.…”
Section: Discussionmentioning
confidence: 94%
“…E148Q was found to be the fourth most common mutation in our cohort. In a recent study by Tirosh et al ( 29 ), it was reported that the presence of the E148Q variant with the M694V variant was not worsening the clinical phenotype. However, M694V/E148Q mutation was found in three of the patients who did not respond to colchicine in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Absence of history of severe attacks ( b ). a E148Q should not be considered as a pathogenic variant [ 10 ] b Severe Attacks = fever and two or more of the following: peritonitis, arthritis, pleuritis, erysipelas like erythema and orchitis …”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that a close clinical and laboratory follow up is required following treatment Table 3 Clinical scenarios that may trigger consideration for colchicine cessation trial when co-exist a E148Q should not be considered as a pathogenic variant [10] b Severe Attacks = fever and two or more of the following: peritonitis, arthritis, pleuritis, erysipelas like erythema and orchitis 1. Patients without biallelic MEFV pathogenic mutations ( a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many published reports from different countries showed that mutations in exon 10 such as M694V, M680I, and V726A are inevitably accompanied by typical clinical manifestations of FMF. However, the effect of mutations in exon 2, specifically the E148Q variant, on phenotype remains an unresolved conundrum [9].…”
Section: Introductionmentioning
confidence: 99%